Trichobezoar with small bowel obstruction in children: Two cases report - Khattala K; Boujraf S; Rami M; Elmadi A; Afifi A; Sbai H; Harandou M; Bouabdallah Y (Wolters Kluwer Medknow Publications, 2008)
A trichobezoar is a mass of cumulated hair within the gastrointestinal tract. Stomach is the common site of occurrence. Intestinal obstruction due to trichobezoar is extremely rare. The authors report two cases of a trichobezoar obstructing the terminal ileum in one and the jejunum in another.